Implementasi Pembelajaran Kooperatif Think Pair Share Guna Meningkatkan Kualitas Pembelajaran Sosiologi - Hamsah (Jurnal Pendidikan Modern, 2021)
Classroom antion research is a study consisting of 2 cycles and 4 stages (planning, action, observation and reflection). Each cycle held 4 meeting in class X IPS, SMA Negeri I Lappariaja Bone Regency with 39 students, 19 boys and 20 girls. This study aims to improve the sociology learning outcomes of the subject of social values ​​and norms by implementing think pair share cooperative learning model. The results of the quantitative analysis show that: (1) The learning outcomes of students in the first cycle are in the medium category with an average score of 65 from the ideal score of 100 with a standard deviation of 10 from the total number of students who complete learning as much as 13 and reach a percentage of 33.3% completeness. (2) Student learning outcomes in cycle II are in the high category with an average score of 79 of the ideal score of 100 with a standard deviation of 9 and the number of students who complete learning is 37 and reaches a percentage of 94.9% completeness. The results of the qualitative analysis describe changes in student attitudes, attendance levels, student activeness and interest during the learning process